Substrate composition influences amino acid carbon isotope profiles of fungi: implications for tracing fungal contributions to food webs. (8th March 2022) - Arsenault, Emily R.; Liew, Jia Huan; Hopkins, Jacob R.
Summary: Fungi link detrital resources and metazoan consumers through their role as decomposers. However, fungal contributions to metazoans may be misestimated in amino acid isotope studies because fungi are capable of both synthesizing amino acids (AAs) de novo and absorbing AAs from their environment. While fungi cultured in AA‐free media have been used to represent fungi in studies of natural environments, fungi likely gain energetic benefits by taking up substrate AAs directly in situ . Consequently, fungi cultured on AA‐free media may not be representative of the true variability of natural fungal δ 13 CAA profiles. Therefore, the objective of this experiment was to determine the effect of substrate AA availability on yeast δ 13 CAA profiles. We found that yeasts cultured in media of relatively higher AA content had different δ 13 CAA profiles than yeasts grown in AA‐free media, in part because yeasts utilized two essential AAs (Leu and Val) directly from media substrates when available in sufficient amounts. Furthermore, these differences among yeast δ 13 CAA profiles remained after normalization of δ 13 CAA values. We recommend further characterization of the variation in fungal δ 13 CAA profiles and the incorporation of this potential variability into interpretations of basal resource use by metazoans.